Pemphigus Foliaceus Autoantibodies Induce Redistribution Primarily of Extradesmosomal Desmoglein 1 in the Cell Membrane - Hiermaier, Matthias; Kugelmann, Daniela; Radeva, Mariya Y.; Didona, Dario; Ghoreschi, Kamran; Farzan, Solimani; Hertl, Michael; Waschke, Jens (Frontiers in Immunology, 2022)
The autoimmune dermatoses pemphigus foliaceus (PF) is predominantly caused by IgG autoantibodies against the desmosomal cadherin desmoglein (Dsg) 1. The exact mechanisms that lead to the characteristic epidermal blistering are not yet fully understood. In the present study, we used a variety of biophysical methods to examine the fate of membrane-bound Dsg1 after incubation with PF patients’ IgG. Dispase-based dissociation assays confirmed that PF-IgG used for this study reduced intercellular adhesion in a manner dependent on phospholipase C (PLC)/Ca2+ and ERK1/2 signaling. Atomic force microscopy (AFM) revealed that Dsg1 binding on single molecule level paralleled effects on keratinocyte adhesion under the different conditions. Stimulated emission depletion (STED) super-resolution microscopy was used to investigate the localization of Dsg1 after PF-IgG incubation for 24 h. Under control conditions, Dsg1 was found to be in part co-localized with desmoplakin and thus inside of desmosomes as well as extra-desmosomal along the cell border. Incubation with PF-IgG reduced the extra-desmosomal Dsg1 fraction. In line with this, fluorescence recovery after photobleaching (FRAP) experiments demonstrated a strongly reduced mobility of Dsg1 in the cell membrane after PF-IgG treatment indicating remaining Dsg1 molecules were primarily located inside desmosomes. Mechanistically, experiments confirmed the involvement of PLC/Ca2+ since inhibition of PLC or 1,4,5-triphosphate (IP3) receptor to reduce cytosolic Ca2+ reverted the effects of PF-IgG on Dsg1 intra-membrane mobility and localization. Taken together, our findings suggest that during the first 24 h PF-IgG induce redistribution predominantly of membrane-bound extradesmosomal Dsg1 in a PLC/Ca2+ dependent manner whereas Dsg1-containing desmosomes remain.